2017
DOI: 10.21548/27-1-1600
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Fungicide Spray Cover on Botrytis Cinerea Infection in Grape Bunches

Abstract: The effect of fungicide spray cover on Botrytis cinerea infection in grape bunches was determined. Bunches were sprayed at pea size and bunch closure with different volumes of a mixture of fenhexamid and a yellow fluorescent pigment, and the percentage fluorescent pigment coverage on pedicels was determined. Bunches were subsequently dusted with dry airborne conidia of B. cinerea in a settling tower and incubated for 24 h at high relative humidity (98%). Infection was determined by estimating the amount of B. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
9
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(10 citation statements)
references
References 13 publications
(21 reference statements)
1
9
0
Order By: Relevance
“…Practical management of these diseases relies almost exclusively on well-timed and/or routine fungicide applications; therefore producers invest heavily in chemical products and spray equipment. Laboratory studies showed that B. cinerea was effectively controlled with the available botryticides, provided that sufficient deposition on susceptible tissue was obtained (Van Rooi, 2001;Van Rooi & Holz, 2003;Brink et al, 2006). Similar efficiency was, however, not achieved when the same fungicides were applied in the vineyards, using conventional spraying methods .…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…Practical management of these diseases relies almost exclusively on well-timed and/or routine fungicide applications; therefore producers invest heavily in chemical products and spray equipment. Laboratory studies showed that B. cinerea was effectively controlled with the available botryticides, provided that sufficient deposition on susceptible tissue was obtained (Van Rooi, 2001;Van Rooi & Holz, 2003;Brink et al, 2006). Similar efficiency was, however, not achieved when the same fungicides were applied in the vineyards, using conventional spraying methods .…”
Section: Introductionmentioning
confidence: 99%
“…Brink et al (2004) developed and validated a spray deposition assessment protocol using fluorometry, photomicrography and digital image analyses to assess spray deposition on susceptible grape bunch parts. Brink et al (2006) used this spray assessment technique in developing a protocol that could be used to determine the effect of different spray deposition levels on B. cinerea incidence. However, they could not determine the minimum effective deposition levels needed for effective control of B. cinerea in grape bunches to be used as spray deposition benchmarks to evaluate spray application in vineyards for the control of this and other important grapevine diseases.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations